Factors Affecting Production Traits in Dairy x Beef Cattle - Idris, Ismail (1990)
Data from 96Angus-Holstein crossbred cows were analysed to study the effects of sire breed of calf, nutrition leve~ weaning age of calf and their interactions an the cows and calves. The cows were assigned to rations either with low or high energy leve~ whik all calves received the same diet until 224 days. Sire breeds used were Guernsey, Longhtfm, Brahman, Hereford and SimmentaL Body weights of cows and calves together with feed consumptions were taken cv"y 28 days whik body measurements were taken cve>y 56 days. Calf weaning age influenced age at first postpartum estrus and TDN consumption of cows. Weaning age also influenced progeny weaning weight and TDN consumption. Similarly, cow body weights at several production Periods were influenced lJy calf weaning age.